Pemurnian Limbah Asam Sitrat Dengan Proses Kalsinasi Untuk Mendapatkan Gipsum - Sumingkrat Sumingkrat; Theresia Elly Witasari (Balai Besar Kimia dan Kemasan, 1996)
Sludge from citric acid industry can be purified to be gypsum. Purification was done by calcination process at the condition 1 atm pressure and 110 °C of temperature to get calcium sulphate hernihydrat or Plester de Paris. Calcium sulphate specification that we got are grew color, hygroscopis, unsoluble in water, unflammable, and will be hard if mixed with water.